Impact of Forest Fires in Sumatra and Kalimantan to Atmospheric Pollution During Period Of 2010-2015 - Dessy Gusnita (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2021)
contribute significantly. Pollutant emissions caused by forest fires comprising CO, SO2 and dust (PM10). This paper will be analyzed estimates of pollutant emissions in both Kalimantan and Sumatra using the estimation method based on the amount of material burned. Estimates of the emissions and dispersion of pollutants such as particulates, sulfur dioxide, carbon monoxide were investigated. Distribution and concentration of pollutants used time series of monthly data and spatial map based on satellite data. Extensive data from the 2010-2014 forest fires data from the ministry of the environment and forestry (KLHK) and forest fire data period 2015 from LAPAN. Pollutant concentration data used AIRS on satellite data, OMI satellite and MERRA during 2010-2011 and in 2014-2015, adjusted to the data in situ vast wildfires for both regions. The results of estimation of pollutant emissions in Sumatra shows emissions from forest fires for the period of 2010 greater than in 2011, reaching 9 tons of CO per year, while emissions from fires and plantations during 2011 were higher than in 2010 with a very high value of 150 Tons/year for pollutants CO. In Kalimantan, emissions from forest fires during 2010-2011 CO emissions highest in West Kalimantan 11.13 tons/year and South Kalimantan 12.14 tons of CO per year. Emissions from fires and plantations in South Kalimantan reached 32.11 tons/year.